Electric submersible centrifugal pump application in the conditions of the reservoir fluids high gas content for Vuktylskoye oil field; Academic Science - Problems and Achievements X; Vol. 2 - Korotchenko R. K. Roman Konstantinovich (2016, 2016)
Title screen